Protective effects of kolaviron and gallic acid against cobalt-chloride-induced cardiorenal dysfunction via suppression of oxidative stress and activation of the ERK signaling pathway (2016)
Cobalt (Co) toxicity is a potential public health problem due to recent renewed use of Co in orthopedic implants, dietary supplements, and blood doping in athletes and horses. We investigated the protective roles of kolaviron (KV), a bi flavonoid of Garcinia kola, and gallic acid (GA) on cobalt chloride (CoCl2)-induced cardiorenal damage in rats. CoCl2 caused significant increases (p < 0.05) in serum creatine kinase–myocardial band (CK-MB), lactate dehydrogenase (LDH), aspartate transaminase (AST), xanthine oxidase (XO), urea, creatinine, malondialdehyde, H2O2, nitric oxide, as well as C-reactive protein expression, along with significant (p < 0.05) reduction in cardiac and renal expression of extracellular signal regulated kinase (ERK) and the activities of superoxide dismutase, catalase, and glutathione S-transferase. KV and GA prevented the toxic effects of CoCl2 by stimulating ERK expression and reversing Co-induced biochemical changes. Administration of CoCl2 alone did not significantly alter ECG patterns in the rats, although co-treatment with KV (200 mg/kg) produced QT-segment prolongation and also appeared to potentiate Co hypotension. Histopathology of the heart and kidneys of rats treated with KV and GA confirmed the biochemical data. KV and GA thus protected against cardiac and renal damage in Co intoxication via antioxidant and (or) cell survival mechanisms, possibly involving ERK activation.